Weighted averaging technique for the design of dynamic vibration absorber installed in damped primary structures - Anh, N. D.; Hai, N. Q.; Nguyen, N. X.; Hieu, D. V.; My, P. T. T. (Vietnam Journal of Mechanics, 2018)
The dynamic vibration absorber (DVA) has been widely applied in various technical fields. This paper presents a simple approach to determine a closed-form expression for the tuning ratio of a DVA attached to a damped primary structure. The result is obtained by using the so-called weighted averaging technique of the equivalent linearization method proposed by the first author. The values of the tuning ratio given in this paper are compared with those obtained numerically as well as the ones obtained from other authors. The comparison shows the reliability of the method given in this study.